Smoking Behavior, Smoking Motivation, Stress, Physical Condition and Health Promotion Behavior of College Students with NO Smoking Intention (Medico Legal Update, 2019)
This study attempted to identify the smoking behavior, smoking motivation, stress and health promotingbehaviors of college students and to analyze basic physical condition and to provide basic data for smokingcessation program of college students. The subjects of this study were 135 college students who were willingto quit smoking. Data collection period was collected from February 1, 2018 to June 30, 2018. Statisticalmethods used were frequency, mean, standard deviation, t-test and ANOVA. Also Pearson's correlation analysisand regression analysis were used. Smoking motives are smoking behavior, key. Systolic blood pressure,hemoglobin, and smoking behavior were significantly correlated with CO 2 concentration. Body weight wassignificantly correlated with height, SBP, DBP, AST, ALT, ?-GTP, and CO 2 concentration and stress. Therewas a statistically significant correlation between SBP, DBP, ALT, hemoglobin, and hematocrit. Leukocytewas significantly correlated with hematocrit, and stress and ?-GTP were also significantly correlated. Healthpromotion activities showed a significant negative correlation with smoking motivation. Blood pressure,hemoglobin, platelet, and stress were found to have a significant effect on health promotion behaviors.Therefore, in order to prevent smoking of college students and help smoking cessation, basic physicalcondition is checked to promote health promotion, smoking cessation program should be developed toreduce smoking motivation.